P002 Advice line ... of duty. (23rd April 2022) - Knight, Lucy; Miller, Joanna; Dahiya, Sandeep
Abstract: Background/Aims: Advice lines in Rheumatology services are well established and supported by NICE to provide specialist support and advice to rheumatology patients. During COVID-19 the demand on this service greatly increased due to disruption in appointments, confusion regarding national advice, concerns and fears regarding condition and medication. Although patients were encouraged to refer to national guidance, many found it difficult to interpret therefore continued to access the advice line. Our advice line service largely follows the RCN 2006 guidance regarding service provision. Despite this during COVID-19 the volume of calls increased to up to 100 calls per day during the first lockdown. Support was required to effectively manage these calls with reduced clinical staff. Methods: A retrospective review of calls to the advice line compared to the previous year was undertaken from the call log database. A further review of the nature of calls was undertaken for April 2020 and January 2021 where the numbers of calls were at their peak. Data is recorded including time of call, nature of call, advice given and time call returned. Results: There was a 130% increase in calls during the first lockdown. This reduced by the early 2021 lockdown to 72%. The majority of calls in April 2020 were related to shielding and risk status (53%). A further 19% of calls were related to medication, these included queries regarding homecare deliveries and delays. 6% were appointment enquiries and they were passed to the administrative team. In January 2021 the majority of calls were related to medication (30%). 19% of calls were regarding the COVID-19 vaccine. There were still 8% of calls regarding shielding. 9% of calls were related to appointments. Pressure on the nursing team was increased due to staff redeployment. Conclusion: The analysis of calls during the COVID-19 pandemic highlighted that although there was extensive national guidance produced, many patients still required the support and guidance of their specialist teams to interpret these according to their condition. We believe there is a duty of care for the specialist teams to maintain this level of service during any future events and this should be factored into any decisions regarding redeployment of staff. Appointments and homecare delivery enquiries continued despite directions to alternate numbers, therefore impacted on workload for the clinical nursing team. In order to streamline the service we introduced 'options' to select: option 1 for appointments, option 2 for homecare and option 3 for advice line queries. Option 1 and 2 then directed to the relevant team. Future developments include audit to assess the impact of introducing telephone options; reviewing the funding and scope of the service, which has extended beyond medication and flare advice; and further exploration of text and email platforms. Disclosure: L. Knight: None. J. Miller: None. S. Dahiya: None.